PEMECAHAN SENYAWA KOMPLEKS DALAM KAOLIN DAN PENGAMBILAN ALUMINA DENGAN METODE KALSINASI DAN ELUTRIASI - -, Sukamta; Budiman, Arif; -, Sutijan; W, Akhmad Bening; Budiharto, Segar (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Caolin or chines clay seldom used in industry, is formed of very little particles especially caolinite, i.e. a mixture of aluminum oxyde (Al2O3), silika oxyde (SiO2) and wa-ter (H2O). Each composition posseses a different characteristic. The article discusses a separation alumina from caolin which was from Semin, Klaten, the midle of Java, by cal-cination and elutriation methods. The calcination method is a separation one by breaking the bond between the substances using heat. In this case, it was used 800oC because at this temperature it reached vitrification point and the complex bond was broken. The sam-ple was dried under the sun, crushed, and screened by multiple screening i.e. 200 mesh, 230 mesh, 270 mesh, 325 mesh and 400 mesh. From the screening process it was ga-thered fraction between 325 and 400 mesh as the most one, therefor this farction was us-ed as a sample. This one then was elutriated with fluid terminal velocity was varied. It was obtanied that the concentration of alumina incresed relatively high at the fluid velovity of 0.1278 cm/s and 0.2117 cm/s i.e. the alumina concentration increased of 5,2% dan 7,4% became 76.81%.